Comparative Study of Privacy-Preserving Measures in Nigerian E-Commerce Platforms (FULAFIA IAC Book of Proceedings, 2024)
Most Nigerian e-commerce today are faced with numerous challenges, primarily due to the pressure that exist between providing e-commerce services and protecting users personalized information. Users’ details provided on these platforms are most times shared with third-party advertisers and analytics companies without users’ consent. Hackers and internet fraudsters take advantage of the weakness of these platforms to obtain account details of users. An assessment of privacy-preserving strategies in Nigerian e-commerce platforms is therefore crucial in the present digital era, when online transactions and data interchange have become indispensable to the corporate environment. Because of the increased attention that privacy problems in e-commerce platforms have received, users of these platforms need to be more aware of how their personal information is treated. This article investigates privacy-preserving methods used by popular e-commerce platforms in Nigeria. The goal of the study is to present a thorough assessment of the level of privacy protection in most commonly used Nigerian e-commerce platforms. The study's recommendations are intended to direct customers, e-commerce companies, and policymakers toward a safer and more secure online buying environment in Nigeria.